1989
DOI: 10.1071/mf9890519
|View full text |Cite
|
Sign up to set email alerts
|

Impact of timber harvesting and production on streams: A review

Abstract: Timber harvesting operations have significant effects on both water quantity and water quality. The effects on water quantity have been well documented both in Australia and elsewhere. The effects on water quality are less widely appreciated, and include elevated concentrations of dissolved salts, suspended solids and nutrients, especially during peak flow periods. Several Australian studies have failed to measure peak flow transport of suspended solids, or have measured it inadequately, thus severely underest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
8

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(118 citation statements)
references
References 68 publications
3
104
0
8
Order By: Relevance
“…The decrease observed in NEP indicates an increase in the net rate of organic carbon consumed (Young et al, 2008). Forest clearfelling can cause inputs of fresh brash into receiving waters (Campbell and Doeg, 1989;Lockaby et al, 1997), stimulating heterotrophic processes (Clapcottt and Barmuta, 2010), and Drinan et al (2013) reported elevated BOD in the GS following clearfelling supporting this theory. Ponce (1974) reported on the high demand for oxygen exerted by microbes associated with fresh brash and mentioned it can rapidly deplete DO concentrations in receiving water.…”
Section: Discussionsupporting
confidence: 55%
“…The decrease observed in NEP indicates an increase in the net rate of organic carbon consumed (Young et al, 2008). Forest clearfelling can cause inputs of fresh brash into receiving waters (Campbell and Doeg, 1989;Lockaby et al, 1997), stimulating heterotrophic processes (Clapcottt and Barmuta, 2010), and Drinan et al (2013) reported elevated BOD in the GS following clearfelling supporting this theory. Ponce (1974) reported on the high demand for oxygen exerted by microbes associated with fresh brash and mentioned it can rapidly deplete DO concentrations in receiving water.…”
Section: Discussionsupporting
confidence: 55%
“…1993). Despite this, little work has been reported specifically examining the efficacy of these management methods in mitigating impacts on streams (Campbell and Doeg 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, little has been published on the effects of Australian forestry operations on stream habitat quality or fauna (Campbell and Doeg 1989;Doeg and Koehn 1990b). Richardson (1985) reported impacts of road sedimentation associated with logging on stream macroinvertebrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the large number of studies that identify direct causal relationships between human activities in catchments and increased sediment loads (e.g. Campbell & Doeg, 1989), the most likely hypothesis relating these factors is that anthropogenic activity in catchments and around estuary margins causes large inputs of fine suspended sediments that are transported to and Estuary group F 4. Scatterplots showing relationships between the faunal disturbance index DI n for sites located in estuaries grouped by morphological and hydrological similarities, human population density in catchments, and the silt/clay content of sediments.…”
Section: Anthropogenic Impacts On Biota In Tasmanian Estuariesmentioning
confidence: 99%